Development of Mathematics Teaching Module Based on Islamic Integrated Resource Based Learning to Improve High School Students' Conceptual Understanding - Siregar, Annisa Fachraini; Ariawan, Rezi; Herlina, Sari; Wahyuni, Reni; Nufus, Hayatun (Jurnal PEKA (Pendidikan Matematika), 2026)
The aim of this study is to develop a mathematics learning module based on the RBL model that incorporates Islamic values, specifically for the topic of compound probability. Additionally, the study seeks to determine whether the module is valid and effective in enhancing students' conceptual understanding. This study was motivated by students' low conceptual understanding of compound probability and the limited availability of independent, Islamic value-integrated learning materials based on RBL syntax. This study employs a Research and Development (R&D) approach based on the 4-D model, which comprises the stages of Define, Design, Develop, and Disseminate. The research subjects consisted of 22 students from class XI at MA IBS Riau. After data were collected using expert validation sheets and pre-test and post-test scores, a descriptive quantitative method was used to analyze them. The results showed that the developed module achieved an overall validity score of 84.29% (categorized as "very valid"). The effectiveness test yielded an average N-Gain score of 0.6914 (moderate category), with 77.3% of students achieving moderate-to-high learning gains and a classical mastery level of 54.55%. These results indicate that the RBL-based mathematics learning module, which incorporates Islamic values ​​into the topic of compound event probability, possesses a satisfactory level of validity and effectiveness. They also demonstrate its suitability as an alternative resource for independent learning, particularly in Islamic boarding schools